Minor Theft: Problems of the Initiation of a Case on an Administrative Offense and Conducting an Administrative Investigation - Oleg Y. Filippov; Andrey E. Yuritsin (Сибирское юридическое обозрение, 2016)
The paper defines the problem of the initiation of an administrative case and conducting an administrative investigation on cases of identifying signs of minor theft under Art. 7.27 of the Code of Administrative Offences of the Russian Federation in cases where the identity of the offender at the time of committing minor theft is not established, this person is not detained. Guidance on the application of this provision under the existing legislation and on amendments and supplements to the law on administrative offenses is offered.